2019
DOI: 10.3389/fgene.2019.00782
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Reduction of Genomic Heterozygosity in an Industrial Yeast Strain Reveals Wide Cryptic Phenotypic Variation

Abstract: Abundant genomic heterozygosity can be found in wild strains of the budding yeast Saccharomyces cerevisiae isolated from industrial and clinical environments. The extent to which heterozygosity influences the phenotypes of these isolates is not fully understood. One such case is the PE-2/JAY270 strain, a natural hybrid widely adopted by sugarcane bioethanol distilleries for its ability to thrive under harsh biotic and abiotic stresses during industrial scale fermentation, however, it is not known whether or ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…VI), consistent with the fact that H3 and H4 originated from sibling spores that were derived via meiosis from the same parental diploid genome. Patterns of LOH across the genome were also previously observed in segregants of JAY270, the parental diploid of JAY291 (Rodrigues-Prause et al, 2018;Sampaio et al, 2019). The higher polymorphism density observed between H3 and H4 along Chrs.…”
Section: H3 H4 and Jay291 Represent Alternative Polymorphic Genomes supporting
confidence: 65%
See 1 more Smart Citation
“…VI), consistent with the fact that H3 and H4 originated from sibling spores that were derived via meiosis from the same parental diploid genome. Patterns of LOH across the genome were also previously observed in segregants of JAY270, the parental diploid of JAY291 (Rodrigues-Prause et al, 2018;Sampaio et al, 2019). The higher polymorphism density observed between H3 and H4 along Chrs.…”
Section: H3 H4 and Jay291 Represent Alternative Polymorphic Genomes supporting
confidence: 65%
“…It is suggested that a homeostatic balance between selective pressures in the complex environment of the distillery tends to maintain the heterozygous state of the genome (Sampaio et al, 2019).…”
Section: Genetic Signatures Of Bioethanol Yeasts and Adaptation To Inmentioning
confidence: 99%
“…The impact on fitness can also be strain dependent, as it is been previously shown that hybrids between different strains of the same species can have different characteristics [23,27]. Under stressful conditions, chromosome aneuploidy, such as full or partial uni-parental disomy, can arise in the genome and also affect the fitness [28,29]. However, in this study, the hybrids have not been evolved or adapted to any particular stress, which makes disomy unlikely.…”
Section: Different Mitochondrial Dna Is Retained In Saccharomyces Hybmentioning
confidence: 79%
“…Our analysis and those of others show that mitotic recombination events are frequent enough to be an important source of diversity. In organisms such as S. cerevisiae, these events will produce variants that may have selective advantages in certain environments (65)(66)(67). In humans, such events can release cells from normal growth regulation, initiating tumor formation.…”
Section: Discussionmentioning
confidence: 99%